Use of the BACTEC Mycobacteria Growth Indicator Tube 960 Automated System for Recovery of Mycobacteria from 9,558 Extrapulmonary Specimens, Including Urine Samples - Hillemann, Doris (American Society for Microbiology, 2006)
The BACTEC Mycobacteria Growth Indicator Tube 960 (MGIT 960) system was applied for recovery of mycobacteria from extrapulmonary specimens and compared with solid media (Löwenstein-Jensen and Stonebrink). A total of 9,558 specimens were investigated, comprising 3,074 body fluids, 1,878 tissues, and 2,069 urine samples, from which the recovery of mycobacteria was not yet established for MGIT 960. In total, the MGIT 960 was able to detect 446 (90.3%) of the 494 isolates of Mycobacterium tuberculosis complex (MTBC) and 223 (86.0%) out of the 259 isolates of nontuberculous mycobacteria (NTM). In comparison to this, culture on solid medium revealed 358 (72.6%) MTBC isolates and 164 (66.8%) NTM isolates. While 136 (27.6%) of the MTBC isolates and 95 (19.2%) of the NTM isolates were recovered from the MGIT 960 only, 48 (9.7%) of the MTBC isolates and 36 (13.9%) NTM isolates grew only on solid media. Thus, the overall sensitivities for the recovery of mycobacteria from extrapulmonary specimens with MGIT 960 and solid media were 88.8% and 69.3%, respectively. However, the efficiency of the MGIT 960 system can be maximized with additional culture on solid media.